Exchange rate regimes in an increasingly integrated world economy - Mussa, Michael...[et al] (IMF WashingtonUS, 2000)
Examines the consequences of heightened capital mobility and of the integration of developing economies in increasingly globalized goods and financial markets for the exchange rate regimes both of the world's major currencies and of developing and transition countries.